Effectiveness of Public Open Spaces for Residents in Gated Communities: Case Study of Citra Wisata Medan Johor - Samuel Simarmata, Hery; Nirfalini Aulia, Dwira; Tamiami Fachrudin, Hilma (Lafadz Jaya Publisher, 2024)
The number of gated community housing is increasing and becoming a popular option in urban areas because of the security and privacy. Public open spaces in housing areas have a crucial role in improving environmental quality and the welfare of residents and the surrounding community. Therefore, this study will analyze the quality and test the effectiveness of Public Open Space research in Gated Community, Case Study of Citra Wisata Medan Johor. This study uses a qualitative approach with 5 variables used, namely; security, comfort, achievement, livability, and image. This study will be conducted for 1 month using 2 data collection methods, namely primary data (Observation and Questionnaire) and secondary data (Literature study). The results of this study are expected to contribute to the field of science, housing developers, housing residents, and the government in terms of the use and benefits of public open spaces in gated community housing.